Comparison of Efficacy of Gow-Gates Mandibular Nerve Block and Inferior Alveolar Nerve Block for The Extraction of Mandibular Molars - Ayesha Maqsood; Muhammad Adil Asim; Fouzia Aslam; Rushna Khalid; Omer Khalid (KARACHI MEDICAL AND DENTAL COLLEGE, 2018)
Objective: The purpose of this study is to compare the efficacy of two local anaesthesia techniques i.e. inferior alveolar nerve block and Gow-Gates nerve block technique in terms of their success rate to anaesthetize tissues, time of onset of action, pain levels during administration and amount of drug used to achieve adequate anaesthesia. Methods:  This randomised control trial was carried out in department of Oral & Maxillofacial Surgery at Rawal Institute of Health Sciences, Islamabad from September 2017 to May 2018. A  total  of  138 patients were selected and randomly allocated to receive Gow-Gates (GG) nerve block or inferior al-   veolar nerve block (IANB) for extraction of mandibular molars. Onset of anaesthesia and success rate was noted for individual nerves. Pain  during  administration  of  anaesthesia  was  compared  between  IANB group and GG group by verbal response scale. Status of blood  aspiration  during  injection and volume of local anaesthesia solution used to  achieve  adequate  anaesthesia  for  extraction  of  lower  molar tooth was also noted at the end of procedure. Results: Comparison of success to achieve anaesthesia did not  show  significant  difference  between IANB and GG groups except the buccal soft tissue. Onset of action of anaesthesia of all nerves (IAN, lin- gual and buccal) was achieved much earlier in IANB. While results of pain and total amount of drug used were significantly better in favor of GG group as shown by p-value of 0.015 and 0.002 respectively. Conclusion: We conclude that GG nerve block is a good alternative technique to conventional IANB technique for extraction of mandibular molars.